High serum level of C-reactive protein is associated with worse outcome of patients with advanced-stage NSCLC treated with erlotinib - Fiala, Ondrej; Pesek, Milos; Finek, Jindrich; Topolcan, Ondrej; Racek, Jaroslav; Minarik, Marek; Benesova, Lucie; Bortlicek, Zbynek; Poprach, Alexandr; Buchler, Tomas (Tumour biology, 2015)
Erlotinib is a low molecular weight tyrosine kinase inhibitor (TKI) directed at epidermal growth factor receptor (EGFR), widely used in the treatment of locally advanced or metastatic-stage non-small cell lung cancer (NSCLC). Although introduction of EGFR-TKIs have significantly extended survival of advanced-stage NSCLC patients, their efficacy in the entire patient population is relatively low. Aside from activating EGFR mutations, no reliable biochemical or molecular predictors of response to erlotinib have been established. The aim of our retrospective study was to evaluate the association of baseline serum levels of C-reactive protein (CRP) with outcomes in patients with advanced-stage NSCLC treated with erlotinib. We retrospectively analyzed clinical data of 595 patients with advanced-stage NSCLC (IIIB or IV) treated with erlotinib. Serum CRP was measured using an immunoturbidimetric method. High baseline levels of CRP (≥10 mg/l) were measured in 387 (65 %) patients, and normal levels (<10 mg/l) were measured in 208 (35 %) patients. The median progression-free survival (PFS) and overall survival (OS) for patients with high CRP was 1.8 and 7.7 compared to 2.8 and 14.4 months for patients with low CRP (p < 0.001 and p < 0.001). The multivariable Cox proportional hazards model revealed that CRP was significantly associated with PFS and also with OS (hazard ratio (HR) = 1.57, p < 0.001, and HR = 1.63, p < 0.001, respectively). In conclusion, the results of the conducted retrospective study suggest that high baseline level of CRP was independently associated with worse outcome of patients with advanced-stage NSCLC treated with erlotinib. CRP is a commonly used biomarker which is simple and easy to detect, and thus, it is feasible for the use in the routine clinical practice.
Keywords: výsledek terapie; Disease-Free Survival; Male; Erlotinib; mutace; NSCLC; Carcinoma, Non-Small-Cell Lung; Erlotinib Hydrochloride; Neoplasm Staging; erlotinib; Prediction; Adult; C-reaktivní protein; Aged; dospělí; mužské pohlaví; senioři; inhibitory proteinkinas; Treatment Outcome; EGFR-TKI; lidé; ženské pohlaví; C-reactive protein; Biomarkers, Tumor; Biomarker; Humans; nemalobuněčný karcinom plic; Lung cancer; Protein Kinase Inhibitors; erbB receptory; C-Reactive Protein; Mutation; Female; ErbB Receptors; lidé středního věku; staging nádorů; nádorové biomarkery; přežití bez známek nemoci; Middle Aged